LIFE Med Hiss: An innovative cohort design for public health - Gandini, Martina; Scarinzi, Cecilia; Bande, Stefano; Berti, Giovanna; Ciancarella, Luisella; Costa, Giuseppe; Demaria, Moreno; Ghigo, Stefania; Marinacci, Chiara; Piersanti, Antonio; Sebastiani, Gabriella; Cadum, Ennio (MethodsX, 2019)
[Display omitted] The aim of MED HISS methodology was to test the effectiveness of a low-cost approach to study long-term effects of air pollution, applicable in all European countries. This approach is potentially exportable to other environmental issues where a cohort representative of the country population is needed. The cohort is derived from the National Health Interview Survey, compulsory in European countries, which has information on individual lifestyle factors. In Life Med Hiss approach, subjects recruited have been linked at individual level with health data and have been then followed-up for mortality and hospital admissions outcomes. Exposure values of air pollution (PM2.5 and NO2) have been assigned using national dispersion models, enhanced by the information derived from monitoring station with data fusion techniques, and then upscaled at municipality level (highest level of detail achievable for the Italian Survey). Results for mortality have been used to test the effectiveness of this methodology and are encouraging if compared with European ones. The advantages of this technique are summarized below: •It uses a cohort already available and compulsory in European countries•It uses air quality modelling data, available for most of the countries•It permits to implement versatile environmental surveillance systems